Verbunden mit den Slaven : Festschrift für Swetlana Mengel - Chelbaeva, Tatjana; Lehmann-Carli, Gabriela (2022)
"Connected with the Slavs" - this leitmotif unites contributions by Slavists and representatives of neighbouring disciplines. Together they show the wealth and impressive range of Slavic research: from language history to current developments in the Slavic languages to literary and cultural history. Among other things, they address the written and standard Slavic languages and their various standardisation processes, the significance of (biblical) translations and grammars, language in the diaspora, intercultural communication and the university certification of language skills, as well as the multifaceted Slavic literature and the cultural bond between the peoples. This volume is dedicated to Prof. Dr. Swetlana Mengel.